British journal of sociology - London School of Economics and Political Science ([Henly-on-Thames, Oxon ; Boston, Mass. : Published by Routledge & Kegan Paul for the London School of Economics and Political Science], 1950)
Access available online from 1999-
Published <2004->: Osney Mead, Oxford : Blackwell Pub.
Keywords: Sociology -- Periodicals; Sociology -- Periodicals; Sociology -- Periodicals; Sociologie -- Périodiques$; Sociologie; SOCIOLOGY; UNITED KINGDOM